2009
DOI: 10.1016/j.neuron.2009.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Fast and Slow Inhibition from Cerebellar Golgi Cells Allow Flexible Control of Synaptic Integration

Abstract: Throughout the brain, multiple interneuron types influence distinct aspects of synaptic processing. Interneuron diversity can thereby promote differential firing from neurons receiving common excitation. In contrast, Golgi cells are the sole interneurons regulating granule cell spiking evoked by mossy fibers, thereby gating inputs to the cerebellar cortex. Here, we examine how this single interneuron type modifies activity in its targets. We find that GABAA-mediated transmission at unitary Golgi cell → granule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 68 publications
7
78
0
Order By: Relevance
“…Although fast stimulus-locked inhibition of granule cells has thus far been difficult to detect in vivo (37), our voltage-clamp recordings revealed sensory-evoked phasic and spillover inhibition in all granule cells, consistent with the view that Golgi cell axons strongly influence many hundreds of granule cells across the granular layer (15,47). Moreover, the prevalence of slow, spillovermediated IPSCs in granule cells suggests that indirect spillover activation of GABA A receptors is a major form of Golgi-cell signaling during sensory stimulation (21,37,48,49). Differences in the number of direct and indirect synaptic inputs in each glomerulus will determine the relative contribution of fast and slow IPSCs during sensory activation (21,30,49).…”
Section: Discussionsupporting
confidence: 84%
“…Although fast stimulus-locked inhibition of granule cells has thus far been difficult to detect in vivo (37), our voltage-clamp recordings revealed sensory-evoked phasic and spillover inhibition in all granule cells, consistent with the view that Golgi cell axons strongly influence many hundreds of granule cells across the granular layer (15,47). Moreover, the prevalence of slow, spillovermediated IPSCs in granule cells suggests that indirect spillover activation of GABA A receptors is a major form of Golgi-cell signaling during sensory stimulation (21,37,48,49). Differences in the number of direct and indirect synaptic inputs in each glomerulus will determine the relative contribution of fast and slow IPSCs during sensory activation (21,30,49).…”
Section: Discussionsupporting
confidence: 84%
“…Although these speculations are intriguing because of the use of serotonergic and antiglutamatergic drugs in PBA, the function of various cells and neurotransmitters within the cerebellar microcircuitry, or their specific role in PBA, has not been clearly defined, and researchers continue their efforts to elucidate potential mechanisms within this circuitry and their potential role in cerebro-cerebellar loops [50][51][52][53].…”
Section: Cerebellar Mechanismsmentioning
confidence: 99%
“…The temporal aspects of GABAergic signaling (e.g., slow versus fast) have distinct computational consequences (Crowley et al, 2009;Pavlov et al, 2009). A previous study in cerebellar granule cells found that tonic GABA A R-mediated conductances affected both offset and gain of the I-O relationship with a noisy input (Mitchell and Silver, 2003).…”
Section: Effects Of Rectification Of the Tonic Conductance On Noise Amentioning
confidence: 99%